2020
DOI: 10.1039/c9sc04294f
|View full text |Cite
|
Sign up to set email alerts
|

Observation of binding of carbon dioxide to nitro-decorated metal–organic frameworks

Abstract: Synergistic effects between –NO2 groups and open metal sites lead to optimal binding of CO2 molecules within MFM-102-NO2via hydrogen bonding to C–H groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…A ν 2 band at 660 cm –1 was detected by synchrotron FTIR micro-spectroscopy after adsorption of CO 2 on MFM-102-NO 2 . At high coverage the band splits into two components (at 663 and 657 cm –1 ) indicating symmetry lowering.…”
Section: Interaction Of Mofs With Guest Moleculesmentioning
confidence: 90%
“…A ν 2 band at 660 cm –1 was detected by synchrotron FTIR micro-spectroscopy after adsorption of CO 2 on MFM-102-NO 2 . At high coverage the band splits into two components (at 663 and 657 cm –1 ) indicating symmetry lowering.…”
Section: Interaction Of Mofs With Guest Moleculesmentioning
confidence: 90%
“…The significant increase in CO 2 adsorption was related to the strong interaction between the –OH groups and CO 2 . Duong et al 109 functionalized MFM-102 with –NO 2 , alkyl and –NH 2 , and found that the CO 2 adsorption capacity of MFM-102-NO 2 increased by 36% to 8.21 mmol g −1 at 273 K, 1 bar. This is because the introduction of –NO 2 not only polarized the adjacent phenyl C–H bonds through the conjugation effect of the aromatic ring, but also created additional adsorption sites for direct dipole/quadrupole interaction.…”
Section: Modification Methods Of Mofs For Co2 Capturementioning
confidence: 99%
“…Developments in gas-handling systems have also paved the way to probe gate-opening and related network-breathing phenomena arising from the unique elastic properties of MOFs—see entries in Table 1 and Refs. [ 151 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: From Confined Polymers To Soft Supramolecular Frameworkmentioning
confidence: 99%